2022
DOI: 10.3390/vaccines10101581
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of Leuconostoc mesenteroides Cell-Free-Supernatant GBUT-21 against SARS-CoV-2

Abstract: The unprecedented health catastrophe derived from the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2 infection) met with a phenomenal scientific response across the globe. Worldwide, the scientific community was focused on finding a cure for the deadly disease. A wide range of research studies has consistently revealed the link between SARS-CoV-2 infection severity and abnormal gut microbiomes, suggesting its potential in developing novel therapeutic approaches. Probiotics have been extensively st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Human colorectal cancer cells were obtained from American Type Cell Culture ATCC, United States, and were used to study the viability of cancer cells mediated by nanoparticles VCrZnO4 ( Alzahrani et al, 2022 ; Rather et al, 2022b ). HEK-293 cells were also used as a control to ensure the effectiveness of the study.…”
Section: Methodsmentioning
confidence: 99%
“…Human colorectal cancer cells were obtained from American Type Cell Culture ATCC, United States, and were used to study the viability of cancer cells mediated by nanoparticles VCrZnO4 ( Alzahrani et al, 2022 ; Rather et al, 2022b ). HEK-293 cells were also used as a control to ensure the effectiveness of the study.…”
Section: Methodsmentioning
confidence: 99%
“…The intricate crosstalk between the commensal microbiota and the immune system can contribute to developing or suppressing infection [ 107 ]. Evidence suggests that host microbiota can influence immunity at mucosal surfaces against a range of viral infections via AMP secretion [ 108 , 109 ], the inhibition of viral attachment to host cells [ 110 , 111 , 112 ], and the modulation of mucosal immune cells [ 113 , 114 ]. In a study by Kim et al, Staphylococcus epidermidis , a common human nasal commensal, was shown to suppress the replication of the influenza A virus in the nasal mucosa of mice [ 115 ].…”
Section: Role Of Host Microbiota In Susceptibility To Viral Infection...mentioning
confidence: 99%
“…Lactiplantibacillus pentosus KAU0010 and Limosilactobacillus fermentum KAU0021 were isolated from fermented ajawa dates of Madinah by following the same method as described elsewhere [24]. The isolation and molecular characterization were carried out following the same procedure described elsewhere [25]. Lactobacillus sakei Probio-65, a well-known commercial probiotic strain isolated from Kimchi, was provided by Dr. Lew Lee Ching, ProBionic, Republic of Korea.…”
Section: Identification and Characterization Of The Lactobacillus Str...mentioning
confidence: 99%